Postdischarge health resource use in pediatric survivors of prolonged mechanical ventilation for acute respiratory illness. Issue 7 (26th April 2022) - Vo, Michelle; Miller, Kristen; Bennett, Tellen D.; Mourani, Peter M.; LaVelle, Jaime; Carpenter, Todd C.; Scott Watson, R.; Pyle, Laura L.; Maddux, Aline B.
Abstract: We aimed to identify characteristics associated with postdischarge health resource use in children without medical complexity who survived an episode of prolonged mechanical ventilation for respiratory illness. We hypothesized that longer durations of mechanical ventilation, noncomplex chronic conditions, and severe acute respiratory distress syndrome (ARDS) would be associated with readmission or an Emergency Department (ED) visit. In this retrospective cohort, we evaluated children without a complex chronic condition who survived a respiratory illness requiring ≥3 days of mechanical ventilation and who had insurance eligibility within the Colorado All Payers Claims Database. We used insurance claims to characterize health resource use and multivariable logistic regression to identify characteristics associated with readmission or an ED visit during the postdischarge year. We evaluated 82 children, median age 12.8 months (interquartile range [IQR]: 4.0–24.1), 20 (24%) with a noncomplex chronic condition and 62 (76%) without any chronic conditions. Bronchiolitis (60%) and pneumonia/aspiration pneumonitis (17%) were the most common etiologies of respiratory failure and 47 (57%) patients had severe ARDS. Forty‐six (56%) patients had an ED visit or readmission. Among the 18 readmitted patients, 16/18 (89%) readmissions were for respiratory illness. Forty (49%) patients had ≥2 outpatient pulmonary visits and 45 (55%) filled a pulmonary medication prescription. In analyses controlling for age, illness severity and mechanical ventilation duration, severe ARDS was predictive of ED visit or readmission (odds ratio [OR]: 5.53 [95% confidence interval [CI]: 1.79, 19.09]). Children who survive prolonged mechanical ventilation for respiratory disease experience high rates of postdischarge health resource use, particularly those surviving severe ARDS.